Disciplina, governamentalidade e virtualidade na sala de aula ampliada: anotações de aprende en casa, a estratégia educacional mexicana em face da pandemia COVID-19 - Cangas, Omar Daniel (2021)
The structure of this essay consists of three sections. The first section refers to the historic weaving that has refined the new corrective technologies of the individual. The second section conceives a critical perspective of the school by comparing it with an industry that produces tame students with manipulable moralities. The third section exemplifies how, even in the extended classroom, the restraint and subjectivation devices of these corrective technologies of the student not only continued to manifest but when imbricated with authority in the family context, seem to increase. In addition, all the sections have been sustained in the sense of some critical student and teachers’ perspectives of what was (and still is), exercising their professional practice living those formative processes from the Aprende en Casa strategy. Furthermore, the sensation, maybe shared, of having lost the essential space for learning accomplishments: school and its classrooms.